Feeding potential of a mycophagous beetle Halyzia tschitscherini (Coleoptera: Coccinellidae) against powdery mildew Phyllactinia corylea in mulberry - Illahi, Irfan; Khan, M.A; Zeya, S.B.; Aslam, M.; Mittal, Vishal (Indian Phytopathology, 2011)
Mulberry diseases are the major constraints in silk cocoon production. Among the diseases in mulberry foliage, powdery mildew caused by Phyllactinia corylea (Pers) Karst reduces the leaf yield up to 20% and is more prevalent during July to November in Kashmir valley. A mycophagous beetle, Halyzia tschitscherini Semenor (Coleoptera: Coccinellidae) inhibit the growth of mulberry powdery mildew mycelia on mulberry leaf lamina. It was observed that different numbers of beetles (2-5) consumed powdery mildew of grade II (1-5 % leaf lamina covered with powdery mildew mycelia) and the whole mycelial patch was cleared off within 36 hours by five beetles (T4). In other set of experiment, five number of beetles consumed powdery mildew i.e of grade II to grade V in different time durations. The observations indicate that the beetles have the potential to consume the highest ratings grade V (i.e. 96.40 cm2) of powdery mildew infection within 60 hours. Consumption of powdery mildew mycelia / hour / beetle was recorded in the range of 0.312 to 1.462 cm2 in different ratings of the powdery mildew infection. Thus, the results indicated that this beetle may be utilized as a biological control agent in seri-ecosystem.